Ahmadiyah: A History and its Religious Conflicts in Indonesia, 1925-2008 - Suyatman, Ujang (TAWARIKH, 2017)
ABSTRACT: Ahmadiyah constitutes the modern movement in Islam, which was founded by Mirza Ghulam Ahmad at Qadian, India (recently, Pakistan) in the early of 19th century. From the earlier development, this school had been procuring the resistances from Islamic majority in India for having and developing some distorted Islamic teachings. Because the vision of the movement is based on the ideas related to the issues of âaqidahâ or basic beliefs in Islam, which includes the concept of Isa al-Masih death, Prophecy, al-Mahdi, and al-Masih al-Mauâud, so Ahmadiyah was also seen as part of the âKalamâ schools science or theology in Islam. Those ideas are what ultimately dragging this stream into the protracted conflicts that occur among Muslims. Since its presence in Indonesia in 1920s, Ahmadiyah had been confronting some various conflicts against the majority of Islamic society. The conflicts were initially limited to the theological debates. However, since the years of 2000s, the conflicts burst out into the physical actions, such as destroying the worshipperâs places and in the end turning up the victims. The conflicts involving Ahmadiyah and the Islamic mainstream continue to grow, even after the issue of SKB (Surat Keputusan Bersama or Joint Decree) of the three Ministers in Indonesia in 2008. This present research, then, is aimed at the description of the history of Ahmadiyah, including the conflict and its problem solving, which are conducted by those who quarreled, especially in West Java, Indonesia.KEY WORDS: Ahmadiyah; Mirza Ghulam Ahmad; Revelation; Prophecy; Religious Conflict.About the Author: Dr. Ujang Suyatman is a Senior Lecturer at the Faculty of Adab and Humanities UIN SGD (State Islamic University, Sunan Gunung Djati) Bandung, Jalan A.H. Nasution No.105 Cipadung, Bandung 40614, West Java, Indonesia. For academic interests, the author is able to be contacted via e-mail at: suyatman806@gmail.comHow to cite this article? Suyatman, Ujang. (2017). âAhmadiyah: A History and its Religious Conflicts in Indonesia, 1925-2008â in TAWARIKH: International Journal for Historical Studies, Vol.8(2) April, pp.203-216. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (January 15, 2017); Revised (March 11, 2017); and Published (April 28, 2017).